Reorientation simplified: A device for recording and reproducing the path of insertion for removable partial dentures - Vaibhav D Kamble; Rambhau D Parkhedkar (Wolters Kluwer Medknow Publications, 2014)
Aim: The record of path of insertion on the dental cast is part of the dentist's work authorization to the dental laboratory technician. The path of insertion record enables the dental technician to replace the cast on a surveyor in the same position that the dentist selected. Analysis of factors that influence the path of insertion should determine a path of insertion that will reduce the potential for dislodgement and promote stability of removable partial denture (RPD). Materials and Methods: The recording of the relation of a cast to a dental surveyor and the transfer of this relationship to the dental laboratory may be done by tripodization, by scoring the base of the cast, or by cementing a reference pin on the cast. Conclusion: Recording the established path of insertion can be difficult when the procedure uses a cemented pin and the casts are mounted in an articulator. This article describes a procedure for innovative dowel pin and sleeve device to record the path of insertion of RPDs, which serves the same purpose as the cemented pin but can be easily removed and replaced.